EFFECTS OF UPPP ON SLEEP APNEA SYNDROME - Asaka, Daiya; Chiba, Shintaro; Hayama, Takashi; Matsuwaki, Yoshinori; Kojima, Junya (JIBI INKOKA TEMBO, 2004)
We studied the therapeutic efficacy of uvulopalatopharygoplasty (UPPP) using apnea-hypopnea index (AHI) in cases diagnosed as obstructive sleep apnea syndrome and treated with UPPP, and report results comparing factors related to UPPP usefulness by classifying patients into complete and incomplete response groups. Subjects were 26 patients diagnosed with obstructive sleep apnea syndrome based on an overnight polysomnography (PSG) test and treated with UPPP from January 2001 to March 2003 and who underwent overnight PSG tests after surgery. Of these, 19 (73.1%) showing improvement exceeding 50% in postoperative AHI, among whom 11 (42.3%) showed a complete response, i.e., AHI improvement exceeding 50% and postoperative AHI of less than 10 times/hour. Incomplete response was seen in 15 (57.7%), i.e., AHI improvement of less than 50% or postoperative AHI of not less than 10 times/hour. The complete response group showed a significantly greater facial axis, reflecting simultaneous leptoprosopia and retrusion, in cephalometric analysis and was significantly younger than the incomplete response group. In addition, the highest hit ratio of 80.8% in predicting therapeutic efficacy by choosing complete or incomplete response was obtained when the cutoff facial axis was arbitrarily set to 84° and age to 42 years old. We concluded that a high UPPP efficacy may be expected in those with a facial axis of not less than 84° and aged not more than 42 years old. Further factors may affect the severity of sleep apnea syndrome and these should also be taken account in diagnosis and therapy.